2018
DOI: 10.14295/cs.v8i3.2257
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen, potassium, calcium and sulfur omission in grass Convert

Abstract: Intensive use of Brazilian pastures without the maintenance of soil fertility has decreased their productivity and favoring the onset of symptoms of nutritional deficiency. The objective of this study was to evaluate the effect of nitrogen, potassium, calcium and sulfur omission in symptomatology, growth and dry mass accumulation in grass Convert. The experiment was conducted in a greenhouse with a completely randomized design, with five treatments and four replications. The treatments were: full nutrient solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…Nutrients omission limited the production of leaves by plants, with the treatment without fertilization being the most limiting for the development of leaves (Figure 1). This result is similar to that of Miranda et al (2017) who observed a smaller leaves number in the omission of these two nutrients. Leaf blade amount present in the plant is highly correlated with the photosynthetic rate, thus, with the increase in leaves number, there is a respective increase in the photosynthetic rate, which positively results in forage mass (MARTUSCELLO et al, 2016;SOUZA et al, 2019).…”
Section: Resultssupporting
confidence: 91%
“…Nutrients omission limited the production of leaves by plants, with the treatment without fertilization being the most limiting for the development of leaves (Figure 1). This result is similar to that of Miranda et al (2017) who observed a smaller leaves number in the omission of these two nutrients. Leaf blade amount present in the plant is highly correlated with the photosynthetic rate, thus, with the increase in leaves number, there is a respective increase in the photosynthetic rate, which positively results in forage mass (MARTUSCELLO et al, 2016;SOUZA et al, 2019).…”
Section: Resultssupporting
confidence: 91%